Screening of Metalloprotease-Producing Thermophilic Bacteria and Optimization of Trace Elements for Enzyme Activity - Mellanie Alia Putri; Anthoni Agustien; Yetty Marlida; Ayumi Rizci Puspita (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: Thermophilic bacteria are potential sources of thermostable enzymes with important applications in biotechnology and industry. Among these enzymes, metalloproteases are of particular interest because their catalytic activity depends on metal ions. This study aimed to screen thermophilic bacterial isolates from hot springs in Solok Regency, West Sumatra, Indonesia, for metalloprotease production and to evaluate the effects of trace elements on metalloprotease activity. Methodology: Four thermophilic bacterial isolates (TUA-104,                   TUA-106, TUA-109, and TUA-113) were cultivated in protease production medium (pH 8.0) at 50oC for 24 hours, and crude enzymes were obtained by centrifugation. Metalloprotease screening was conducted using EDTA inhibition assays through well diffusion and specific protease activity analyses. The isolate showing the strongest metalloprotease characteristics was further evaluated using 5 ppm Ca²⁺, Mn²⁺, and Zn²⁺ supplementation. Findings: The results showed that isolates TUA-106, TUA-109, and TUA-113 exhibited characteristics of metalloprotease-producing bacteria. Among them, TUA-106 showed the most consistent inhibition pattern, with specific activity decreasing from 0.780 U/mg in the control to 0.522 U/mg after treatment with 10 mM EDTA. Zn²⁺ produced the highest specific activity (0.284 U/mg), followed by Mn²⁺ (0.263 U/mg), whereas Ca²⁺ resulted in the lowest activity (0.036 U/mg). Contribution: These findings indicate that TUA-106 is a potential Zn-dependent metalloprotease-producing thermophilic bacterium and provide new insight into the metalloprotease-producing potential of thermophilic bacteria from Solok geothermal environments for future biotechnological applications